Object Lessons in a time of tolerable suboptimisation. (April 2023) - Bliss, James
The present contribution reflects on the stakes of Robyn Wiegman's Object Lessons (2012) in the wake of a long era of austerity in American higher education. It reflects further on the history of discourses on the relationship between the practice of criticism and radical politics.